2015
DOI: 10.7314/apjcp.2015.16.16.6967
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use Increases Oxidative DNA Damage in Sperm - Possible Etiology of Childhood Cancer

Abstract: Background: Cigarette smoking and tobacco chewing are common modes of consuming tobacco all over the world. Parents need to be aware that germ cell integrity is vital for birth of healthy offspring as biological parenting begins much before birth of a child and even before conception. The present study was conducted to determine the etiology of non-familial sporadic heritable retinoblastoma (NFSHRb), by evaluating oxidative sperm DNA damage in fathers due to use of tobacco (smoking and chewing). Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 28 publications
3
48
1
3
Order By: Relevance
“…The cut-off values for seminal oxidative stress biomarkers, that is, ROS, DFI, and 8-OH2dG, were taken from the study previously published by Kumar et al (2016). 20 The standard semen parameters such as sperm motility, count, and morphology were found to be comparable in fathers of RB patients and healthy controls.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The cut-off values for seminal oxidative stress biomarkers, that is, ROS, DFI, and 8-OH2dG, were taken from the study previously published by Kumar et al (2016). 20 The standard semen parameters such as sperm motility, count, and morphology were found to be comparable in fathers of RB patients and healthy controls.…”
Section: Resultsmentioning
confidence: 85%
“…This suggested that oxidative stress and oxidative DNA damage may serve as a possible etiological factor for the causation of sporadic nonfamilial heritable RB. 20 Therefore, we may conclude that factors like advanced paternal age and poor lifestyle habits may contribute to the generation of oxidative stress in the male germline. This, together with MTHFR polymorphisms, causes aberrant DNA methylation patterns in the sperm DNA and further increases the oxidative stress by decreasing the glutathione production.…”
Section: Introductionmentioning
confidence: 99%
“…DNA Fragmentation Index was performed at the judgment of the attending physician especially in cases of risk factors for abnormal DFI (ex. Smoking [21]) and abnormal semen analysis according to WHO criteria [22]. …”
Section: Methodsmentioning
confidence: 99%
“…Over the past years, numerous studies have emphasised on significant associations between poor sperm DNA integrity and impaired fertilisation (Jin et al., ), deteriorated implantation and early embryogenesis (Simon et al., ), miscarriages (Coughlan et al., ), birth defects and childhood cancers (Kumar, Chawla, Bisht, Yadav, & Dada, ). In general, most of these conclusions are derived from a static sperm DNA damage assessment obtained after ejaculation in fertile as well as infertile men.…”
Section: Discussionmentioning
confidence: 99%